OPTIMALISASI PEMBERDAYAAN KELOMPOK URBAN FARMING UNTUK MENINGKATKAN KETAHANAN PANGAN PASCA PANDEMI COVID-19 - Churiyah, Madziatul; Dharma, Buyung Adi; Sholikhan (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2022)
This study aims to describe the skills of managing agriculture for urban farming groups in the village of Keben Permai Malang after receiving empowerment through mentoring and training on how to manage agriculture. These skills include skills in cultivating land, making planting media, caring for plants, making natural fertilizers, harvesting, and processing post-harvest production. The population of this research is the urban farming group in the village of Keben Permai Malang, which consists of 20 people. This research is an action research, namely providing action in the form of empowerment through mentoring and training. Data on farm management skills are obtained through observation sheets of farm management skills. Data analysis used descriptive analysis. The results showed that the skills of managing agriculture for the urban farming group of Kampung Keben Permai Malang in the category are very good, which means members of the Keben Permai urban farming group already have very good skills to manage agriculture.